Book reviews: Preamble - Laura Steckley (Scottish Journal of Residential Child Care)
When Mark Smith's Rethinking Residential Child Care came out, I was keen to ask Pat Petrie, Professor of Education at the Thomas Coram Research Unit, to review it for the journal. Pat's considerable research and writing experience offer alternative ways of thinking about children's services, and within that, residential child care. Around the same time, Zachari Duncalf, our (then new) Research Fellow, approached me with an interest in reviewing the book. Zachari is not only a bright and energetic addition to SIRCC, but she has considerable personal experience of residential child care--as a young resident during a period of her youth. So I decided to do something different with book review for this edition of the journal. Zachari and Pat have each provided their review of the book, and each has a different perspective on it. We will invite Mark Smith to respond in the next issue of the journal.